Therapeutic Management of Acute Pancreatitis in Three Dogs - Venkatesh, Atmakur; Sumathi, Devaraju; Mohanambal, Kaliyannan; Kavithakumari, Umesh Gupta; Ravi, Ramasamy; Swamy , Kallipatti Karupusamy Ponnu (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The pancreas is a tubuloalveolar gland (Watson, 2015) situated in the right cranial quadrant caudal to the stomach, composed of a left limb or lobe, which lies behind the greater curvature of the stomach and adjacent to the cranial aspect of the transverse colon; a right limb or lobe which lies just medial to the proximal duodenum and a body between these two limbs. It is composed of two types of cells responsible for endocrine and exocrine functions. The major function of the exocrine pancreas is the production, storage, and secretion of digestive enzymes important for the degradation of ingested proteins, fats, and polysaccharides which are subsequently released into the stomach and/or small intestine as food reaches these organs. The digestive enzymes produced by the pancreatic acinar cells are stored until the pancreas is stimulated to secrete them into the duodenum. Acute pancreatitis typically presents as a sudden, sterile inflammation marked by necrosis and edema. This condition does not cause permanent damage to the pancreatic structure and is entirely reversible. It is believed that acute pancreatitis arises mainly due to the improper activation of zymogens within the pancreas, leading to autodigestion, inflammation, and tissue necrosis. This document reports successful therapeutic management of acute pancreatitis in three dogs.